Socialization of Cricket to Physical Education Students University of Bengkulu - yahya eko nopiyanto; defliyanto defliyanto; septian raibowo; bogy restu ilahi (Jurnal Humanities Pengabdian Kepada Masyarakat, 2020)
The purpose of the socialization of cricket was increased the knowledge of physical education students about the development of cricket in Indonesia and improved the skills of physical education students in playing cricket. The socialization activity was carried out in the physical education study program, University of Bengkulu. Partners in this activity were second semester physical education students, totaling 35 students. This activity was carried out on March 14-15 2020. The forms of activities carried out were socialization and practicum. This activity was carried out with a model of small group discussion, lectures and demonstrations. The stages carried out in this activity consist of three stages, namely: socialization, practicum, and evaluation. Based on the results of the activities and the results of the evaluation, it can be concluded that the socialization of cricket to physical education students increased knowledge about cricket and skills in playing cricket.